Thermally activated charge transport in microbial protein nanowires - Lampa-Pastirk, Sanela; Veazey, Joshua P.; Walsh, Kathleen A.; Feliciano, Gustavo T. [UNESP]; Steidl, Rebecca J.; Tessmer, Stuart H.; Reguera, Gemma (Springer Nature, 2016)
The bacterium Geobacter sulfurreducens requires the expression of conductive protein filaments or pili to respire extracellular electron acceptors such as iron oxides and uranium and to wire electroactive biofilms, but the contribution of the protein fiber to charge transport has remained elusive. Here we demonstrate efficient long-range charge transport along individual pili purified free of metal and redox organic cofactors at rates high enough to satisfy the respiratory rates of the cell. Carrier characteristics were within the orders reported for organic semiconductors (mobility) and inorganic nanowires (concentration), and resistivity was within the lower ranges reported for moderately doped silicon nanowires. However, the pilus conductance and the carrier mobility decreased when one of the tyrosines of the predicted axial multistep hopping path was replaced with an alanine. Furthermore, low temperature scanning tunneling microscopy demonstrated the thermal dependence of the differential conductance at the low voltages that operate in biological systems. The results thus provide evidence for thermally activated multistep hopping as the mechanism that allows Geobacter pili to function as protein nanowires between the cell and extracellular electron acceptors.